Outpatient care for facial palsy—a survey on patient satisfaction in uni- and interdisciplinary approaches - Machetanz, Kathrin; Oberle, Linda; Wang, Sophie S.; Weinbrenner, Eliane; Gorbachuk, Mykola; Lauer, Henrik; Daigeler, Adrien; Tatagiba, Marcos; Naros, Georgios; Schäfer, Ruth C. (Frontiers in Neurology, 2024)
Objective The various causes of facial palsy, diagnostic methods and treatment approaches frequently involve different medical specialities. Nevertheless, there exist only few specialized consultation and therapy services for patients with facial palsy (FP) in Germany. The aim of the present study was to evaluate factors affecting quality of life (QoL) and treatment satisfaction of patients presenting to an interdisciplinary facial nerve outpatient clinic. Methods The study analyzed patients presenting to the interdisciplinary facial palsy outpatient clinic in Tuebingen between February 2019 and December 2022. General satisfaction and QoL was estimated by numerous self-rating questionnaires: ZUF-8, SF-36, FDI, FaCE, PHQ-9. An ANOVA was performed to analyze determinants affecting the ZUF-8. Correlation analyses between cause and regeneration of FP as well as questionnaire scores were performed. Results were compared with a group of patients who were managed in an unidisciplinary setting. Results In total, 66 patients with FP were enrolled. FP patients showed increased levels of depression (PHQ-9: 14.52 ± 3.8) correlating with recovery of the palsy (p = 0.008), FaCE (p < 0.001) and FDI ratings (p < 0.001). There was a high level of satisfaction with the services provided during the uni-and interdisciplinary consultation (ZUF-8: 24.59 ± 6.2), especially among the 12/66 patients who received reconstructive, surgical treatment. However, some patients requested more psychological and ophthalmological support. Conclusion High levels of treatment satisfaction can be achieved in both an uni-and interdisciplinary setting. However, multimodal therapy approaches should be applied, considering physical and psychological aspects. In the absence of recovery, surgical interventions must be considered as treatment options. Further studies should continue to investigate potential differences between uni-and interdisciplinary treatment.